Fabrication and Ex-vivo Evaluation of Olanzapine Nanoparticles Based Dissolved Microneedle for Transdermal Delivery - AL-shaibani, Abulfadhel jaber neamah; Ghareeb, Mowafaq M. (Iraqi Journal of Pharmaceutical Sciences, 2025)
AbstractOlanzapine (OLZ) is classified as a typical antipsychotic drug utilized for treatment of schizophrenia, it possesses poor oral bioavailability (60%) due to low solubility and first-pass hepatic metabolism. Hence, the aim of present work is to fabricate and evaluate an olanzapine nanoparticle dissolved microneedles for transdermal delivery to overcome the problems that associated with drug orally, in addition to the ease of administering the medication for schizophrenic patients. Nanoprecipitation method was employed for preparation of olanzapine nanoparticles by using different polymers with various ratios. Nanoparticles were evaluated by several characterization studies such as particle size, polydispersity index(PDI), entrapment efficiency and zeta potential and an in vitro release study. The morphology of nanoparticle was screened by field emission scanning electron microscope (FESEM). Dissolved Microneedle (MN) patch was fabricated by loading of olanzapine nanodispersion into polydimethylsiloxane (PDMS) micromolds cavities, followed by casting the polymeric solution of polyvinylpyrrolidone(PVP-K30) and polyvinyl alcohol (PVA) to form the microneedle matrix, the prepared microneedle patches were evaluated for morphology, mechanical strength, drug content and ex vivo permeation study. The results reveal that olanzapine nanoparticles was in nano-size scale ranged from 70.12nm to 344nm, PDI values range (0.152-0.404), entrapment efficiency ranged from 53.2% to 78.4%, the highest zeta potential value was (-19.01mV) for olanzapine nanoparticle (OLZ-5), that exhibits higher and significant release of drug (P<0.05). FESEM shows spherical shape of nanoparticle with size similar to that obtained by zetasizer. According to the results of nanoparticles, the formula (OLZ-5) considered as optimized formula and utilized for fabrication of microneedle. The results of microneedle fabrication indicate that MN-4 exhibits a sharp needle with good mechanical strength according to texture analysis, high drug content (98.52%), ex vivo permeation study exhibits that MN-4 permeate more effectively through the skin as compared to the simple patch by approximately 5.16 folds. It can be concluded that microneedle patch (MN-4) considered as promising formula to overcome the problems associated with drug orally and could enhance its bioavailability, in addition to improve patient compliance.